Dielectric Modification of 5V‐Class Cathodes for High‐Voltage All‐Solid‐State Lithium Batteries. Issue 9 (4th March 2014) - Yada, Chihiro; Ohmori, Akihiro; Ide, Kazuto; Yamasaki, Hisatsugu; Kato, Takehisa; Saito, Toshiya; Sagane, Fumihiro; Iriyama, Yasutoshi
<x xml:space="preserve">Abstract</x> A "5V‐class" all‐solid‐state lithium battery (Li/Li3.2PO3.8N0.2/LiCr0.05Ni0.45Mn1.5O4‐δ) demonstrates an improved rate capability when its electrolyte/cathode interface is modified by dielectric BaTiO3 nanoparticles. Such "dielectric modification" is supposed to be able to resolve a Li+‐deficient layer at the interface, which has limited the charge‐transfer reactions rates. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>